Physical violence and verbal abuse against nurses working with risk stratification: characteristics, related factors, and consequences - Joyce Borges Ceballos; Oleci Pereira Frota; Hevelyn Francielle Soares Souto Nunes; Patricia Lima Ávalos; Camila de Carvalho Krügel; Marcos Antonio Ferreira Júnior; Elen Ferraz Teston (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: to analyze the characteristics, related factors, and consequences of physical violence and verbal abuse against nurses working with risk stratification. Methods: a cross-sectional, descriptive and quantitative study carried out with 80 nurses who work with risk stratification in emergency services. Data were collected using an adapted instrument and analyzed using (uni)bivariate inferential statistics. Results: companions were the main perpetrators of verbal abuse (86.1%); and patients inflicted physical violence (100%). Professionals with up to five years of experience are 74% less likely to suffer physical violence (p=0.029). Women suffer 5.83 times more verbal abuse than men (p=0.026). Sadness (15.8%) and fear of the aggressor (15.3%) were the main consequences of verbal abuse; and fear of the aggressor (22.2%) and stress (22.2%) were results of physical violence. Conclusion: violence is influenced by institutional, professional and client aspects. Therefore, coping with it requires multidimensional strategies.